Gender Roles in Household Legume Utilization for Complementary Feeding in Dedza and Ntcheu Districts of Malawi - Ministry of Agriculture, Irrigation and Water Development; Lilongwe University of Agriculture & Natural Resources; Michigan State University (International Food Policy Research Institute, 2017)
This study contains data from the survey conducted to assess gender roles in household legume utilization for complementary feeding in Dedza and Ntcheu districts of Malawi.